Long-Term Outcomes With Pharmacological Ovarian Suppression During Chemotherapy in Premenopausal Early Breast Cancer Patients. (25th November 2021) - Lambertini, Matteo; Boni, Luca; Michelotti, Andrea; Magnolfi, Emanuela; Cogoni, Alessio Aligi; Mosconi, Anna Maria; Giordano, Monica; Garrone, Ornella; Arpino, Grazia; Poggio, Francesca; Cinacchi, Paola; Bighin, Claudia; et al.
Abstract: Background: Although use of gonadotropin-releasing hormone agonist (GnRHa) during chemotherapy is an established strategy to protect ovarian function in premenopausal breast cancer patients, no long-term safety data are available, raising some concerns in women with hormone receptor–positive disease. There are controversial data on its fertility preservation potential. Methods: The Prevention of Menopause Induced by Chemotherapy: a Study in Early Breast Cancer Patients—Gruppo Italiano Mammella 6 (PROMISE-GIM6) trial is a multicenter, randomized, open-label, phase III superiority trial conducted at 16 Italian centers from October 2003 to January 2008. Eligible patients were randomly assigned to (neo)adjuvant chemotherapy alone (control arm) or combined with the GnRHa triptorelin (GnRHa arm). The primary planned endpoint was incidence of chemotherapy-induced premature ovarian insufficiency. Post hoc endpoints were disease-free survival (DFS), overall survival (OS), and post-treatment pregnancies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated. Results: Of 281 randomly assigned patients, 80.4% had hormone receptor–positive breast cancer. Median follow-up was 12.4 years (interquartile range = 11.3-13.2 years). No differences in 12-year DFS (65.7% [95% CI = 57.0% to 73.1%] in the GnRHa arm vs 69.2% [95% CI = 60.3% to 76.5%] in the control arm; HR = 1.16, 95% CI = 0.76 to 1.77) or in 12-year OS (81.2% [95% CI = 73.6% to 86.8%] in the GnRHa arm vs 81.3% [95% CI = 73.1% to 87.2%] in the control arm; HR = 1.17, 95% CI = 0.67 to 2.03) were observed. In patients with hormone receptor–positive disease, the hazard ratio was 1.02 (95% CI = 0.63 to 1.63) for DFS and 1.12 (95% CI = 0.59 to 2.11) for OS. In the GnRHa and control arms, 9 and 4 patients had a posttreatment pregnancy, respectively (HR = 2.14, 95% CI = 0.66 to 6.92). Conclusions: Final analysis of the PROMISE-GIM6 trial provides reassuring results on the safety of GnRHa use during chemotherapy as a strategy to preserve ovarian function in premenopausal patients with early breast cancer, including those with hormone receptor–positive disease.